SISTEM INFORMASI BERBASIS WEB PADA TOKO AMI SASIRANGAN BANJARMASIN - Sri Imelda (At-Tadbir : jurnal ilmiah manajemen, 2017)
The purpose of Developing the Web-based Information System At Ami Sasirangan outlet is to analyze Information System by using pieches-method, designing sales information system using DBMS and SDLC and implement web-based application program information system and mysql. The results indicate that the computerized system will facilitate Ami Sasirangan outlet to immediately handle customer problems such as limitations of previous purchases that able to be done with the buyer came directly to the Shop Ami Sasirangan. Development of Information Systems Sales Reports, Stocks and Financial Statements On Ami Sasirangan Shop Web-Based. Menu in built applications such as Home Menu, Product menu, Categories menu, Transaction menu, Finance Report menu, and Log In menu. On the Transaction menu there is Purchasing menu and Sales menu. Keyword: information system, DBMS, SDLC, Ami Sasirangan